Liquid biopsy: a non‐invasive approach for Hodgkin lymphoma genotyping. (27th July 2021) - Alcoceba, Miguel; García‐Álvarez, María; Chillón, M. Carmen; Jiménez, Cristina; Medina, Alejandro; Antón, Alicia; Blanco, Oscar; Díaz, Luis G.; Tamayo, Pilar; González‐Calle, Verónica; Vidal, María Jesús; Cuello, Rebeca; et al.
Summary: The Hodgkin lymphoma (HL) genomic landscape is hardly known due to the scarcity of tumour cells in the tissue. Liquid biopsy employing circulating tumour DNA (ctDNA) can emerge as an alternative tool for non‐invasive genotyping. By using a custom next generation sequencing (NGS) panel in combination with unique molecule identifiers, we aimed to identify somatic variants in the ctDNA of 60 HL at diagnosis. A total of 277 variants were detected in 36 of the 49 samples (73·5%) with a good quality ctDNA sample. The median number of variants detected per patient was five (range 1–23) with a median variant allele frequency of 4·2% (0·84–28%). Genotyping revealed somatic variants in the following genes: SOCS1 ( 28%), IGLL5 (26%), TNFAIP3 (23%), GNA13 (23%), STAT6 (21%) and B2M ( 19%). Moreover, several poor prognosis features (high LDH, low serum albumin, B‐symptoms, IPI ≥ 3 or at an advanced stage) were related to significantly higher amounts of ctDNA. Variant detection in ctDNA by NGS is a feasible approach to depict the genetic features of HL patients at diagnosis. Our data favour the implementation of liquid biopsy genotyping for the routine evaluation of HL patients.